Meet the press. March 21, 2010 - Boehner, John, 1949-; Hoyer, Steny H. (Steny Hamilton), 1939-; Kaine, Timothy M.; Steele, Michael S.; Todd, Chuck, 1972-; Smiley, Tavis, 1964-; Gillespie, Ed; Dunn, Anita, 1958-; Gregory, David, 1970-; Martin, Betsy Fischer (New York, NY : NBCUniversal, 2010)
On this edition of Meet the Press: Congressmen Steny Hoyer and John Boehner discuss the upcoming House vote on health care; Democratic Party Chairman, Tim Kaine and Republican Party Chariman, Michael Steele discuss the Obama presidency; insights and analysis from Chuck Todd, Tavis Smiley, Ed Gillespie, and Anita Dunn.
Title from resource description page (viewed Aug. 14, 2014).
Broadcast Mar. 21, 2010.
In English.
Keywords: Obama, Barack; Public health -- United States; Presidents -- America; Press conferences; Television news programs